‘If I had not taken it [HIVST kit] home, my husband would not have come to the facility to test for HIV’: HIV self-testing perceptions, delivery strategies, and post-test experiences among pregnant women and their male partners in Central Uganda - Joseph K. B. Matovu; Rose Kisa; Esther Buregyeya; Harriet Chemusto; Shaban Mugerwa; William Musoke; Caroline J. Vrana; Angela M. Malek; Jeffrey E. Korte; Rhoda K. Wanyenze (Global Health Action, 2018)
Background: HIV self-testing (HIVST) can improve HIV-testing rates in ‘hard-to-reach’ populations, including men. We explored HIVST perceptions, delivery strategies, and post-test experiences among pregnant women and their male partners in Central Uganda. Methods: This was a qualitative study implemented as part of a pilot, cluster-randomized oral HIVST intervention trial among 1,514 pregnant women attending antenatal care services at three health facilities in Central Uganda. The qualitative component of the study was conducted between February and March 2017. We conducted 32 in-depth interviews to document women and men’s perceptions about HIVST, strategies used by women in delivering the kits to their male partners, male partners’ reactions to receiving kits from their female partners, and positive and negative social outcomes post-test. All interviews were audio-recorded, transcribed verbatim, and analyzed manually following a thematic framework approach. Results: Women were initially anxious about their male partners’ reaction if they brought HIVST kits home, but the majority eventually managed to deliver the kits to them successfully. Women who had some level of apprehension used a variety of strategies to deliver the kits including placing the kits in locations that would arouse male partners’ inquisitiveness or waited for ‘opportune’ moments when their husbands were likely to be more receptive. A few (three) women lied about the purpose of the test kit (testing for syphilis and other illnesses) while one woman stealthily took a mucosal swab from the husband. Most men initially doubted the ability of oral HIVST kits to test for HIV, but this did not stop them from using them. Both men and women perceived HIVST as an opportunity to learn about each other’s HIV status. No serious adverse events were reported post-test. Conclusion: Our findings lend further credence to previous findings regarding the feasibility of female-delivered HIVST to improve male partner HIV testing in sub-Saharan Africa. However, support for women in challenging relationships is required to minimize potential for deception and coercion.